Phage therapy for recurrent urinary tract infections: A qualitative study using the theoretical framework of acceptability - David Wenzel; Michelle Crick; Carolyn Tarrant; Olivia Revitt; Jeni Senior; Melissa Haines (PLoS ONE, 2026)
Objectives To explore the anticipated acceptability of bacteriophage therapy for recurrent urinary tract infections (rUTIs) among key stakeholders in the United Kingdom, using the Theoretical Framework of Acceptability (TFA). Design Qualitative study using online focus groups, analysed with reflexive thematic analysis, and mapped to the constructs of the TFA. Setting United Kingdom, conducted online via Microsoft Teams. Participants Forty-four participants across three stakeholder groups: individuals with lived experience of rUTIs, doctors involved in UTI management, and other healthcare professionals (HCPs: specialist nurses, pharmacists, and advanced care practitioners). Results Participants demonstrated high enthusiasm for phage therapy, reflecting positive affective attitude and strong perceptions of effectiveness. For patients with lived experience, enthusiasm was often grounded in desperation following repeated treatment failure, raising ethical concerns around vulnerability to poor-quality research or inequitable access. Across groups, opportunity costs were identified as key barriers, centred on financial impact and availability within the NHS. Gaps in understanding about mechanisms, safety, and delivery highlighted the importance of intervention coherence and, for doctors and other HCPs, self-efficacy. Lived experience participants described strong online communities that acted as informal knowledge networks, suggesting a potential channel for dissemination and education. Conclusions Phage therapy was broadly viewed as acceptable, but acceptability is conditional on evidence of safety and effectiveness, equitable access, and clear communication. Application of the TFA demonstrated how enthusiasm, vulnerability, cost, and coherence intersect to shape overall perceptions. These findings emphasise the importance of ethical safeguards, patient-centred education, and integration with community networks to support the responsible adoption of phage therapy.